2018
DOI: 10.1007/s00018-018-2784-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of proinflammatory macrophage activation

Abstract: In the last decade, metabolism has been recognized as a major determinant of immunological processes. During an inflammatory response, macrophages undergo striking changes in their metabolism. This metabolic reprogramming is governed by a complex interplay between metabolic enzymes and metabolites of different pathways and represents the basis for proper macrophage function. It is now evident that these changes go far beyond the well-known Warburg effect and the perturbation of metabolic targets is being inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 135 publications
(201 reference statements)
2
90
0
1
Order By: Relevance
“…Innate immunity constitutes the first line of defense against pathogen infection and contributes to the activation of adaptive immune response for a more potent protection. Macrophages with a critical role in innate immunity respond rapidly to the pathogens, after, they undergo a transition from their classical highly inflammatory phenotype to a less inflammatory state to limit the damage and promote tissue repair . Although the mechanisms responsible for these changes are still not completely understood, it is believed that metabolic reprogramming is a major cause .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immunity constitutes the first line of defense against pathogen infection and contributes to the activation of adaptive immune response for a more potent protection. Macrophages with a critical role in innate immunity respond rapidly to the pathogens, after, they undergo a transition from their classical highly inflammatory phenotype to a less inflammatory state to limit the damage and promote tissue repair . Although the mechanisms responsible for these changes are still not completely understood, it is believed that metabolic reprogramming is a major cause .…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages with a critical role in innate immunity respond rapidly to the pathogens, after, they undergo a transition from their classical highly inflammatory phenotype to a less inflammatory state to limit the damage and promote tissue repair. 1 Although the mechanisms responsible for these changes are still not completely understood, it is believed that metabolic reprogramming is a major cause. 2 Activated macrophages are known to undergo extensive metabolic reprogramming with substantial accumulation of cellular metabolites such as itaconate.…”
Section: Introductionmentioning
confidence: 99%
“…228 Permeable itaconate and 4-octyl itaconate (OI) restricted the type 1 IFN response and the production of inflammatory cytokines by macrophages. 47,48 OI was tested in PBMCs from lupus patients in which it decreased the production of pro-inflammatory cytokines, such as TNFα and IL-6, through the activation of NRF2 signaling. 229 These important recent developments in immunometabolism research should lead the implementation of studies to test whether Krebs cycle metabolite intermediates that have secondary immune signaling functions could be targeted in lupus.…”
Section: Multiple Parameters Of Mt Dysfunction Have Been Reported Inmentioning
confidence: 99%
“…Mechanistically, itaconate derivatives can regulate nuclear factor kappa B inhibitor zeta (IκBζ) via activating transcription factor 3 (ATF3), ameliorating IL-17 IκBζ-driven inflammation [76]. Further, cell-permeable itaconate derivatives decreased cytokine production in macrophages and limited the type I IFN response, indicating a possible therapeutic use for itaconate and its derivatives in IFN-driven diseases such as SLE [77,78]. Further, cell-permeable itaconate derivatives decreased cytokine production in macrophages and limited the type I IFN response, indicating a possible therapeutic use for itaconate and its derivatives in IFN-driven diseases such as SLE [77,78].…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
“…Another study identified that activation of nuclear factor-like 2 (Nrf2) via Kelch-like ECH-associated protein 1 (KEAP1) alkylation could explain the anti-inflammatory effects exhibited by itaconate [77]. Further, cell-permeable itaconate derivatives decreased cytokine production in macrophages and limited the type I IFN response, indicating a possible therapeutic use for itaconate and its derivatives in IFN-driven diseases such as SLE [77,78].…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%